Aplikasi Layanan Pengaduan Siswa SMA/SMK Di Berbasis Android - Reski, Tri; Esabella, Shinta (Management of Information System Journal, 2023)
SMA/SMK IN Sumbawa Regency in the complaint process is carried out manually, that is students have to make complaints manually, namely meeting the BK teacher and telling what is being complained about, and resulting in all problems not being conveyed clearly to the KCD DIKBUD, The author's goal is to design and build Android-based Application for High School/Vocational High School Student Guidance Services in Sumbawa Regency (Case Study of the Education and Culture Office Branch Office of Sumbawa Regency, West Nusa Tenggara), which can be accessed directly by Android-based students, and for web-based admins, the KCD DIKBUD so that it can improve complaint services more effectively and efficiently for students and the KCD DIKBUD. The results of this study are Applications for High School/Vocational High School Student Guidance Services in Sumbawa Regency based on Android using the waterfall software development method, modeling using Data Flow Diagrams (DFD), and Dart language flutter and using black box testing.